Person-centred ostomy care: a qualitative study of patients’ experiences with routine use of a clinical feedback system during consultations - Lill Anette Juvik; John Roger Andersen; Kirsten Lerum Indrebø; Anne Marie Sandvoll (Journal of Patient-Reported Outcomes)
Abstract Background Adapting to life with an ostomy can be challenging due to significant bodily changes. To better meet patients’ needs and support their adjustment, a clinical feedback system (CFS) with patient-reported outcomes was developed for routine outpatient follow-up consultations with stoma care nurses (SCNs) in specialist health care services. While results from its use prior to consultations are promising, little is known about patients’ perceptions of CFS use in consultations with SCNs. Thus, we aimed to explore how patients experience the routine use of the CFS during follow-up consultations in ostomy care. Methods An inductive qualitative design was employed, involving semi-structured individual interviews with 27 patients using the CFS as part of routine care. Data were analysed using reflexive thematic analysis. Results The overarching theme, “A flexible, engaged, person-centred follow-up,” was developed, along with four themes: (1) Explicit and implicit use of information in consultations, (2) A springboard for deeper dialogue on sensitive issues, (3) Reassurance that changes in health status will be captured and adequately assessed, and (4) Utility depends on continuity of use. There were variations in how patients experienced their responses being utilised by the SCNs during consultations. Responses were referenced implicitly and explicitly, with a preference for direct communication. Patients found personal value in using the CFS, as it facilitated communication, particularly on sensitive topics. SCNs’ use of the CFS and expertise provided a sense of reassurance when health status was assessed. Regular use of the CFS and a clear understanding of its purpose enhanced its utility and enabled patients to take a more active role in their treatment. Conclusion The use of the CFS in ostomy care appears promising. It can improve SCNs’ ability to tailor care to patients’ needs. However, the tool should be applied consistently to realise its full potential in clinical practice.